Evaluación técnico-financiera para la producción del aceite de açaí partiendo de los residuos del proceso de despulpado para Green and Inclusive Group SAS. (2020)
The current investigation has as its purpose the technical-financial evaluation of the process to obtain açaí oil starting from the waste from the pulping process of this fruit on a laboratory scale, which was carried out under the directional parameters of the Technopark of the SIGN. It should be noted that there are different types of oils, depending on their origin, they are classified into vegetable or animal oils, and these are highly desired in the industry due to their nutritional contribution, which contributes to giving added value to different traditional products, whether for human consumption or for body care. Açaí is a low-consumption fruit locally, currently the companies that process this fruit are marketing it in the form of hearts of palm, pulp and derived products.